Chromosome‐level de novo genome assembly of Sarcophaga peregrina provides insights into the evolutionary adaptation of flesh flies. (15th September 2020) - Ren, Lipin; Shang, Yanjie; Yang, Li; Wang, Shiwen; Wang, Xiang; Chen, Shan; Bao, Zhigui; An, Dong; Meng, Fanming; Cai, Jifeng; Guo, Yadong
Abstract: Sarcophaga peregrina is considered to be of great ecological, medical and forensic significance, and has unusual biological characteristics such as an ovoviviparous reproductive pattern and adaptation to feed on carrion. The availability of a high‐quality genome will help to further reveal the mechanisms underlying these charcateristics. Here we present a de novo‐assembled genome at chromosome scale for S. peregrina . The final assembled genome was 560.31 Mb with contig N50 of 3.84 Mb. Hi‐C scaffolding reliably anchored six pseudochromosomes, accounting for 97.76% of the assembled genome. Moreover, 45.70% of repeat elements were identified in the genome. A total of 14, 476 protein‐coding genes were functionally annotated, accounting for 92.14% of all predicted genes. Phylogenetic analysis indicated that S. peregrina and S. bullata diverged ~ 7.14 million years ago. Comparative genomic analysis revealed expanded and positively selected genes related to biological features that aid in clarifying its ovoviviparous reproduction and carrion‐feeding adaptations, such as lipid metabolism, olfactory receptor activity, antioxidant enzymes, proteolysis and serine‐type endopeptidase activity. Protein‐coding genes associated with ovoviparity, such as yolk proteins, transferrin and acid sphingomyelinase, were identified. This study provides a valuable genomic resource for S. peregrina, and sheds insight into further revealing the underlying molecular mechanisms of adaptive evolution.